THE PROBLEM OF GENERATION AND TIME IN PHILOSOPHY AND DAILY CONSCIOUSNESS: Әлеуметтік философия (Journal of Philosophy Culture and Political Science, 2022)
In this article, the category of generation was considered as an attribute of a person’s social life. In the course of work the ideas of Aristotle, one of the founders of philosophical science, representatives of German philosophy I.Kant and A.Schopenhauer, about the generation and their role and period in time, were studied. In particular, Aristotle views a man as a freedom-loving creature living in continuous motion. The magnitude of this movement is to determine its time by a person in which Aristotle explores activity in two directions: one biological, the other social. The direction of studying the surname, generation of a person in the past and present can be found in the works of I.Kant, A.Schopenhauer. The goal is to achieve a new stage of social change through the upbringing of a person, including the achievement of social and legal significance especially the level of a state. In the current generation of Kazakhstan, external objective situations, trends, and situations where they are aware of their internal time and associate it with social activity predominate. This ability makes young people go astray in understanding the essence and significance of the country. Therefore, it is difficult for the younger generation to assess their future. Because I.Kant defines the nature of posterity as his foresight. A.Schopenhauer is an individual, it is a subject that creates movement in one direction which, through self-identification, through the study of himself, cognizes others.K.Jaspers studies that an individual who listens to others and considers other people to be significant, valuable in society, creates a certain environment associated with his nation, population and spiritual traditions.